(3COhGQ GdTQhbs - (3GdbQGaj , CMeO Hf GOQjS Hf YHO GdQMef, TgGH GdOjf CHh GdYHGS,J (B684 (3g` s
(3ChdgG (B:s
(3hHYO aEf hSejJg COhGQ GdTQhb s
(3BNQgG (B:s
(3CQHYhf PQGYkG bGd Ydjg GdSdGe s
(3Vef eLehY , JQJjHgG (B: (3GdKGfis
(3HgG fXGe GdJYbjHIs
(3hQO GdYfhGf GdCUdi ai c X HQbe (B186/1s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B94 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B158s
Keywords: (3CUhd Gdabgs